Coordination of di- and triimine ligands at ruthenium(II) and ruthenium(III) centers: structural, electrochemical and radical scavenging studies. Issue 10 (18th May 2016) - Booysen, Irvin N.; Adebisi, Abimbola; Akerman, Matthew P.; Munro, Orde Q.; Xulu, Bheki
Abstract: Herein, we explore the coordination of di- and triimine chelators at ruthenium(II) and ruthenium(III) centers. The reactions of 2, 6- bis -((4-tetrahydropyranimino)methyl)pyridine (thppy), N 1, N 2 - bis ((3-chromone)methylene)benzene-1, 2-diamine (chb), and tris -((1 H -pyrrol-2-ylmethylene)ethane)amine (H3 pym) with trans -[Ru II Cl2 (PPh3 )3 ] afforded the diamagnetic ruthenium(II) complex cis -[RuCl2 (thppy)(PPh3 )] (1 ) and the paramagnetic complexes [ mer -Ru2 ( μ -chb)Cl6 (PPh3 )2 ] (2 ), and [Ru(pym)] (3 ), respectively. The complexes were characterized by IR, NMR, and UV–vis spectroscopy and molar conductivity measurements. The structures were confirmed by single crystal X-ray diffraction studies. The redox properties of the metal complexes were probed via cyclic- and squarewave voltammetry. Finally, the radical scavenging capabilities of the metal complexes towards the NO and 2, 2-di(4- tert -octylphenyl)-1-picrylhydrazyl (DPPH) radicals were investigated Abstract :